2014
DOI: 10.4141/cjas2013-136
|View full text |Cite
|
Sign up to set email alerts
|

Effects of transport time and location within truck on skin bruises and meat quality of market weight pigs in two seasons

Abstract: Scheeren, M. B., Gonyou, H. W., Brown, J., Weschenfelder, A. V. and Faucitano, L. 2014. Effects of transport time and location within truck on skin bruises and meat quality of market weight pigs in two seasons. Can. J. Anim. Sci. 94: 71–78. The effects of season (winter vs. summer), transport time (T: 6, 12 and 18 h) and truck compartment (C) on skin bruise score and meat quality were evaluated in 384 pigs distributed across the top front (C1), top back (C4), middle front (C5) and bottom rear (C10) compartment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
3
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 21 publications
0
21
3
2
Order By: Relevance
“…Gosàlvez et al [ 15 ] reported a higher incidence of bruised carcasses in pigs transported in winter and in autumn. Scheeren et al [ 13 ] hypothesize that the greater proportion of skin damage in winter is linked to the tendency of pigs to stand during transportation to avoid making contact with the cold floor and walls of the trailer. Dalla Costa et al [ 25 ] found that pigs were more difficult to handle in winter and need more coercion, which led to more handling-induced bruises.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gosàlvez et al [ 15 ] reported a higher incidence of bruised carcasses in pigs transported in winter and in autumn. Scheeren et al [ 13 ] hypothesize that the greater proportion of skin damage in winter is linked to the tendency of pigs to stand during transportation to avoid making contact with the cold floor and walls of the trailer. Dalla Costa et al [ 25 ] found that pigs were more difficult to handle in winter and need more coercion, which led to more handling-induced bruises.…”
Section: Resultsmentioning
confidence: 99%
“…The effect of the season on pig welfare and carcass quality have been also reported [ 11 , 12 ]. The frequency of skin blemishes, hematomas and blood splashing was shown to increase in winter, probably caused by slips and falls due to slippery icy floor [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Table 3, the pigs slaughtered in winter had the highest skin lesion score, pH 45 value, and incidence of DFD meat (P <0.05). Over winter, the most important causes for a higher proportion of carcasses with skin lesions are falls and slips at unloading (Correa et al, 2013) and in particular during transportation (Scheeren et al, 2014). In addition, a higher proportion of heavier pigs were slaughtered in winter.…”
Section: Resultsmentioning
confidence: 99%
“…Environmental conditions during transport, that also affect skin blemishes and meat quality, include the position of the animal inside the vehicle [6,7]. Pigs located in the front and rear compartments or in the upper and lower decks showed an increased number of carcass skin bruises and a reduced pork quality [8]. Despite several studies on the influence of the environmental conditions during long-distance transports on pig welfare and carcass quality, few studies have investigated these effects during short-distance transports.…”
Section: Introductionmentioning
confidence: 99%